Empathy in Females With Autism Spectrum Disorder - Stroth, Sanna; Paye, Lena; Kamp-Becker, Inge; Wermter, Anne-Kathrin; Krach, Sören; Paulus, Frieder M.; Müller-Pinzler, Laura (Frontiers in Psychiatry, 2019)
Objective: Despite the fact that Autism Spectrum Disorder (ASD) is a common psychiatric diagnosis, knowledge about the special behavioral and neurobiological female phenotype is still scarce. The present study aimed to investigate neural correlates of empathy for physical and social pain and to assess the impact of egocentric perspective taking on social pain empathy in complex social situations in women and girls with ASD. Methods: Nine female individuals with high functioning ASD were compared to nine matched peers without ASD during two fMRI experiments, examining empathy for physical and social pain using well-established paradigms. Participants viewed multiple pictorial stimuli depicting a social target in either physically painful or socially unpleasant situations. In the social situations the participant either shared the social target’s knowledge about the inappropriateness of the situation (observed social target is aware about the embarrassment of the situation; e.g. tripping in public) or not (observed social target is unaware about the embarrassment of the situation; e.g. open zipper). Results: Females with ASD did not rate the physical pain stimuli differently from non-clinical controls. Social pain situations, however, posed a greater challenge to females with ASD: For non-shared knowledge situations females with ASD rated the social target’s embarrassment as more intense. Thus, compared to non-clinical controls females with ASD had a stronger egocentric perspective of the situation rather than sharing the social target’s perspective. On the neural systems level, both groups showed activation of areas of the so-called empathy network that was attenuated in females with ASD during empathy for physical and social pain with a particular reduction in insula activation. Conclusion: Females with high functioning ASD are able to share another person’s physical or social pain on the neural systems level. However, hypoactivation of the anterior insula in contrast to individuals without ASD suggests that they are less able to rely on their shared representations of emotions along with difficulties to take over a person’s perspective and to make a clear distinction between their own and someone else’s experience of embarrassment.